Toleransi Berbagai Varietas Tebu terhadap Penggenangan pada Fase Bibit Berdasarkan Karakter Morfologi dan Anatomi - Avivi, Sholeh; Syamsunihar, Anang; Soeparjono, Sigit; Chozin, dan Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Identification of Indonesia sugarcane varieties tolerant to waterlogging has not been done extensively. Information on varieties tolerant to waterlogging is required for seedling establishment in waterlogged areas. The purpose of this research was to identify the sugarcane varieties responses to several duration levels of waterlogging at seedling stage. The planting materials used were collection of Sugar Factory Semboro including VMC 76-16, BL, PS 862, PS 864, and PS 881. This research was arranged in randomized complete block design (RCBD) with two factors and three replications. The first factor was 5 varieties; the second factor was waterlogging treatment with four levels, i.e. without waterlogging, 2, 4, and 6 weeks of waterlogging in the bucket. The results showed different level of tolerance to water logging among the varities. PS 881 and VMC 76-16 varieties were the most tolerant to waterlogging supported by its ability to maintain plant height, root volume, root and shoot dry weight after been waterlogged for 6 weeks. These varieties were also able to establish aerenchyme tissue and increased the stomatal density. PS 862 was the least tolerant variety to waterlogging. Keywords: aerenchyme, morphology, stomatal density, waterlogging, water stress